2022
DOI: 10.1007/s10792-022-02576-z
|View full text |Cite
|
Sign up to set email alerts
|

Systemic biomarkers of retinopathy of prematurity in preterm babies

Abstract: Purpose Retinopathy of prematurity (ROP) progression is an inter-play of various perinatal and neonatal angiogenic and inflammatory cytokines . A small subset of ROP progresses to ROP requiring treatment. The present study was conducted with the aim to determine whether levels of IL-6, IL-8 and VEGF in serum and urine at the time of first ROP screening visit could be a biomarker for the prediction of development of treatable ROP. Method Prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…However, other studies have reported no significant differences in the level of the vitreous humor of RANTES-CCL5 between controls and ROP infants,[ 21 ] decreased levels in serum,[ 48 ] and blood[ 49 ] of ROP infants. An increased IL-8 level in the tear fluid of ROP infants in the current is supported by reports that have also shown an increase in the IL-8 levels in the vitreous humor,[ 21 ] aqueous humor,[ 50 ] tear fluid,[ 21 ] serum,[ 51 ] and blood[ 52 ] of ROP infants. A study reported that the levels of IL-8 in the urine were not significantly different between control pre-term infants and ROP infants.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, other studies have reported no significant differences in the level of the vitreous humor of RANTES-CCL5 between controls and ROP infants,[ 21 ] decreased levels in serum,[ 48 ] and blood[ 49 ] of ROP infants. An increased IL-8 level in the tear fluid of ROP infants in the current is supported by reports that have also shown an increase in the IL-8 levels in the vitreous humor,[ 21 ] aqueous humor,[ 50 ] tear fluid,[ 21 ] serum,[ 51 ] and blood[ 52 ] of ROP infants. A study reported that the levels of IL-8 in the urine were not significantly different between control pre-term infants and ROP infants.…”
Section: Discussionsupporting
confidence: 82%
“…A study reported that the levels of IL-8 in the urine were not significantly different between control pre-term infants and ROP infants. [ 51 ] Studies have also reported conflicting observations with reference to the levels of IL-8 in amniotic fluid, with one study demonstrating a significant increase[ 53 ] and the other with no significant difference[ 54 ] between controls and ROP infants. Various reports have also shown differences in the observation with reference to IL-6 and MCP1-CCL2 levels in ROP infants.…”
Section: Discussionmentioning
confidence: 99%
“…In a rat OIR model, increased expression of an IL-8 homologue was noted during the peak time points of neovascularization [ 38 ]. Accordingly, a few studies have also demonstrated the correlation between high plasma/serum IL-8 levels in preterm infants after birth and the later development of severe ROP [ 30 , 39 , 40 ].…”
Section: Cytokines: Characteristics and Actionsmentioning
confidence: 99%
“…Nonetheless, published data remained inconclusive regarding the systemic levels of VEGF in association with ROP. Among preterm neonates who eventually developed ROP, some researchers found that VEGF concentrations in the early period of life in cord blood at birth and circulating blood are significantly lower than those in their non-ROP counterparts [ 72 , 85 , 86 ], while some observed the opposite results [ 87 , 88 , 89 ] and others found no difference [ 40 , 58 , 90 ].…”
Section: Cytokines: Characteristics and Actionsmentioning
confidence: 99%
“…The retina of newborns is underdeveloped and has an avascular zone. The pathology has two phases: first, it has an avascular zone owing to hyperoxia or fluctuating oxygen levels, and second, the avascular zone of retina results in a high concentration of vascular endothelial growth factor (VEGF), which promotes the formation of abnormal vasculature (5). The medication used for intravitreal injections include ranibizumab and bevacizumab (6), which are anti-VEGF, both have shown low prevalence of developing refractive errors in the future although bevacizumab-treated eyes in severe cases of ROP were linked to a higher likelihood of myopia or neurodevelopmental damage (7).…”
Section: Introductionmentioning
confidence: 99%